A fast algorithm to delineate watershed boundaries for simple geometries. (December 2020) - Haag, Scott; Schwartz, Daniel; Shakibajahromi, Bahareh; Campagna, Michael; Shokoufandeh, Ali
Abstract: In this manuscript, we describe a computational model to delineate watershed boundaries for simple geometries (points, lines or polygons) where maximum water flow distance can be constrained by a user-defined variable. This method generalizes earlier research to delineate watershed boundaries using a marching algorithm. Our proposed method allows users to delineate watersheds for a number of use-cases including evaluating best management practices (BMP's), measuring water impacts to municipal, city and parcel boundaries and others. We describe computational complexity and space costs and compare them experimentally to standard techniques. Highlights: We present an algorithm that returns watershed boundaries for any single geometric object given a Digital Elevation Model. Empirical tests show that this method is 500 times faster than existing techniques. We present a variation of this algorithm that returns a constrained watershed based on a maximum water flow distance.